When churn happens in a middle east telecom operator - Oliveira, João (2013)
The purpose of this article is to study in detail the relationship between customer and supplier, using a data mining system to detect and define the concept of the churn customer in the telecommunications sector. Research was carried out using a real database of a telecommunications company in the Middle East, after thorough cleaning and auditing with respect to the robustness of the data and its validity within its market. The outcome of this work is the acquisition of acknowledgment on the building, understanding and definition of the churn customer, starting by defining customers with a high probability of leaving the company, and eventually identifying the loyal customers who represent higher profits.